Educational Park Planning in Berkeley, California, 1965-1968 - Brillinger, Matthew (Université d'Ottawa / University of Ottawa, 2016)
Promoted as state-of-the-art desegregation devices, educational parks were large campus-like schools designed and sited to draw students from many neighborhoods. In the mid-1960s, the educational park movement featured prominently in debates about race and education in the United States, winning the support of numerous influential individuals and organizations, yet today the educational park movement is nearly forgotten, akin to a wave that swelled, crested, and crashed, leaving only a muddy wash. How could so many thoughtful and energetic people—1960s educational park advocates—work so hard yet achieve so little? This question can only be answered by reference to a wide-ranging 1960s debate about the appropriate role of the federal government in public education, a debate during which educational parks became emblematic of a federal government intent on remaking public schools to advance its own socially progressive ends. Whereas advocates for an expanded federal role in public education portrayed educational parks as cutting-edge alternatives to outdated and inequitable neighborhood schools, opponents of federalism in education presented the parks as staging areas for federal invasions of old-line school districts. In the end it was the latter vision—with its scenes of federal officials revising textbooks and drawing up lesson plans—that won the day, transforming educational parks into menacing symbols of federal overreach.
Keywords: Educational Parks; Desegregation; Berkeley, California